Fiber from coconut as smart materials in road construction - Wan Noor Hin, Mior Sani; Asnif Hakimi, Azman; Jusma, Jaafar; Indra Mawardi, .; Norhidayah, Abdul Hassan; Mohd Hazree, Hashim (Popular Scientist, 2024)
This study investigates the effects of incorporating coconut fiber as a sustainable modifier in bitumen mixtures, focusing on its impact on mechanical properties such as Marshall stability, indirect tensile strength (ITS), flow, stiffness, and abrasion resistance. Coconut fiber was added at varying percentages (0%, 0.50%, 0.75%, and 1%) to evaluate its performance. The Marshall stability results revealed a significant improvement at 1% fiber content, achieving the highest stability of 11.978 kN, while ITS exhibited a strong polynomial correlation (R2 =0.9818) with fiber content, peaking at 423 kPa for the same fiber percentage. Flow and stiffness showed non-linear trends, with optimal results observed at specific fiber levels, reflecting the complex interaction between fiber dispersion and matrix bonding. Abrasion loss analysis indicated that lower fiber percentages (0.50%) enhanced wear resistance, while higher contents (1%) improved structural integrity but increased susceptibility to wear. The findings highlight that 1% coconut fiber content provides the best balance between mechanical strength and durability, offering a promising approach for enhancing bitumen performance in sustainable road construction. These results underscore the potential of coconut fiber as a cost-effective and environmentally friendly material for improving the performance of bituminous mixtures, aligning with sustainable development goals.